An effective third harmonic generator using a left‐handed nonlinear transmisson line. Issue 3 (March 2014) - Kim, In Bok; Kim, Kang Wook; Yoo, Hyoungsuk; Park, Jonghoo; Kim, Hongjoon
ABSTRACT In this article, an effective third harmonic generator using a left‐handed nonlinear transmission line (LH NLTL) is presented. The proposed harmonic generator using the LH NLTL is composed of a series of varactor diodes and shunt inductances, which were implemented with a 0.2‐mm wide microstrip line. The harmonic generator was built on a Rogers RO4003 substrate and has dimensions of 12 × 7 mm2. The fabricated LH NLTL provides a maximum insertion loss of 5.2 dB, and a minimum insertion loss of 2.2 dB for a wide frequency band from 2.3 to 18.7 GHz. The measured minimum third harmonic conversion loss was 14.2 dB at an input frequency of 2.5 GHz. When compared to other works, a better third harmonic conversion efficiency is achieved with much smaller size in lower frequencies. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:568–570, 2014